2012
DOI: 10.1158/1078-0432.ccr-11-3091
|View full text |Cite
|
Sign up to set email alerts
|

MARCKS Regulates Growth and Radiation Sensitivity and Is a Novel Prognostic Factor for Glioma

Abstract: Purpose This study assessed whether Myristoylated Alanine Rich C-Kinase Substrate (MARCKS) can regulate glioblastoma (GBM) growth, radiation sensitivity and clinical outcome. Experimental Design MARCKS protein levels were analyzed in five GBM explant cell lines and eight patient-derived xenograft tumors by immunoblot, and these levels were correlated to proliferation rates and intracranial growth rates, respectively. Manipulation of MARCKS protein levels was assessed by lentiviral-mediated shRNA knockdown in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 40 publications
(57 reference statements)
5
67
0
Order By: Relevance
“…A study on the role of MARCKS as a tumor suppressor in glioma is consistent with this proposition. 20 In contrast, following phosphorylation at the PSD, phosphorylated MARCKS promotes the activation of AKT due to releasing PIP2 pools. 28,42 Such a dual contribution of MARCKS may explain why an upregulation of MARCKS would not necessarily contribute to tumorigenesis, 20,32 whereas an increase in MARCKS phosphorylation would.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the role of MARCKS as a tumor suppressor in glioma is consistent with this proposition. 20 In contrast, following phosphorylation at the PSD, phosphorylated MARCKS promotes the activation of AKT due to releasing PIP2 pools. 28,42 Such a dual contribution of MARCKS may explain why an upregulation of MARCKS would not necessarily contribute to tumorigenesis, 20,32 whereas an increase in MARCKS phosphorylation would.…”
Section: Discussionmentioning
confidence: 99%
“…20 In contrast, following phosphorylation at the PSD, phosphorylated MARCKS promotes the activation of AKT due to releasing PIP2 pools. 28,42 Such a dual contribution of MARCKS may explain why an upregulation of MARCKS would not necessarily contribute to tumorigenesis, 20,32 whereas an increase in MARCKS phosphorylation would. 22,23,26 By reducing MARCKS phosphorylation and trapping PIP2 pools at the membrane, MPS effectively inactivates the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of MARCKS activity not only reduces airway mucus hypersecretion both in vitro and in vivo (3,5), but also represses inflammatory leukocyte migration and degranulation (6, 7). There have been limited studies on MARCKS in cancer metastasis, but the results have been conflicting (8)(9)(10)(11)(12)(13). This is because MARCKS expression is ubiquitous in various normal and tumor tissues.…”
Section: To the Editormentioning
confidence: 99%
“…Several of these actin-binding proteins are up-or down-regulated in metastatic cell lines and tumours. In particular , recent studies have identified Myristoylat ed Alanine-Ric h C Kinase Substrate (MARCKS) to be implicate d in the pathogenesis of various malignancies such as pituitary and thyroid cancer [3], breast cancer [4], melanoma [5], glioblastoma multiform e cancer [6,7], and cholangiocarci noma [8].…”
Section: Introductionmentioning
confidence: 99%